Relationship between health literacy and body mass index among Arab women with polycystic ovary syndrome - Yazed Sulaiman Al-Ruthia; Bander Balkhi; Sultan AlGhadeer; Wael Mansy; Hisham AlSanawi; Reem AlGasem; Lama AlMutairi; Ibrahim Sales (Elsevier, 2017)
Background: Polycystic ovary syndrome (PCOS) puts patients at higher risk for obesity and diabetes. Poor health literacy is also associated with these conditions. Notably, weight loss is associated with improved ovulation and pregnancy rates for women with PCOS. In this study the association between health literacy and body mass index (BMI) among women with PCOS was examined. Methods: The health literacy of women with PCOS was measured using the Arabic version of the single item literacy screener (SILS) at a university medical center. Sociodemographic and medical information was collected by interviewing the participants and reviewing their medical records, respectively. The relationship between health literacy and BMI was assessed by multiple logistic regression analysis. Results: Health literacy was assessed in 127 women with PCOS from September 2015 to February 2016. Only 16.54% of participants had limited health literacy. The mean BMI for all participants was 30.57 (kg/m2), and the mean age was 27.40 years. Further, most of the participants (74%) had a high school diploma or a higher degree. Almost 56% of the participants were taking metformin, and 11.81% had hypothyroidism. After controlling for age, education, hypothyroidism diagnosis, and the use of metformin, participants with high BMI were 10% less likely to have a good health literacy level (OR = 0.904; 95% CI = 0.829-0.987; P = 0.0238). Conclusion: Improving the health literacy of patients with PCOS may have a positive impact on their BMI and eventually lead to favorable health outcomes.